The Regulatory Mechanism of Sexual Development in Decapod Crustaceans - Farhadi, Ardavan; Cui, Wenxiao; Zheng, Huaiping; Li, Shengkang; Zhang, Yueling; Ikhwanuddin, Mhd; Ma, Hongyu (Frontiers in Marine Science, 2021)
Crustacean culture has been developing rapidly in various parts of the world. Therefore, it is important to understand their reproductive biology. Insulin-like androgenic gland hormone (IAG) secreted from the androgenic gland (AG) is widely accepted as a key regulator of sexual differentiation in male crustaceans. However, recently several sex-related genes (i.e., CFSH, DEAD-box family, Tra-2, Sxl, Dsx, Fem-1, Sox gene family, Foxl2, and Dmrt gene family) have been identified via transcriptomic analysis in crustaceans, indicating that sexual differentiation in crustaceans is more complicated than previously expected. It has been found that several non-coding RNAs (i.e., miRNAs, lncRNAs, and piRNAs) and IAG receptors may be involved in the sexual development of decapods. Identification and study of the regulation mechanism of sex-related genes, non-coding RNAs, and IAG receptors will provide valuable information regarding sexual development in decapods. In this review, the roles of hormonal and genetic factors in both males and females are discussed. In males, crustacean female sex hormone (CFSH), Sxl, Dmrt gene family, Dsx, Sox gene family, GEM, Fem-1, l-GnRH-III, and corazonin play important roles in IAG regulation in the “eyestalk-IAG-testis” endocrine axis. Unlike males, the regulation mechanism and interaction of sexual genes are relatively unknown in females. However, CFSH, IAG, Fem-1, FAMeT, Slo, UCHLs, Erk2, Cdc2, EGFR, Vg, VgR, and VIH seem to play crucial roles during ovarian development. This study summarizes the available information in the field, highlights gaps, and lays the foundations for further studies and a better understanding of the regulatory mechanism of sexual development in decapods.